2021
DOI: 10.1182/bloodadvances.2021004645
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter analysis of geriatric fitness and real-world outcomes in older patients with classical Hodgkin lymphoma

Abstract: We performed a multicenter retrospective analysis across 10 US academic medical centers (2010 - 2018) to evaluate current treatment patterns and outcomes in patients age ≥60 with classical Hodgkin lymphoma (cHL). Among 244 eligible patients, median age was 68, 63% had advanced stage (III/IV), 14% had ECOG performance status (PS) 2-4, and 12% had documented loss of ≥1 activity of daily living (ADLs). Medical comorbidities were assessed by the Cumulative Illness Rating Scale - Geriatric (CIRS-G), where n=44 (18%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“… 13 , 21 The importance of comorbidity measures was highlighted in a recent multicenter analysis, which reported higher rates of toxicity-related early treatment discontinuation in older adults with a Cumulative Illness Rating Scale-Geriatric score ≥10 (28% vs 12%, P = .016) or with documented geriatric syndrome (28% vs 13%, P = .02) treated with conventional therapy, as well as higher mortality from causes other than disease or treatment. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 13 , 21 The importance of comorbidity measures was highlighted in a recent multicenter analysis, which reported higher rates of toxicity-related early treatment discontinuation in older adults with a Cumulative Illness Rating Scale-Geriatric score ≥10 (28% vs 12%, P = .016) or with documented geriatric syndrome (28% vs 13%, P = .02) treated with conventional therapy, as well as higher mortality from causes other than disease or treatment. 22 …”
Section: Discussionmentioning
confidence: 99%
“…cHL in patients over 60 years of age is highly linked to poorer prognosis since these patients generally suffer from inferior efficacy but great toxicity, owing to comorbidity and geriatric fitness ( 12 ). The management of older patients should be individualized and usually requires clinical judgment.…”
Section: Current Standard Treatment Of R/r Chlmentioning
confidence: 99%
“…Interestingly, disability status was not found to be a significant predictor, possibly due to patient selection bias (i.e., only fit patients offered ABVD regimen). Orellana-Noia et al carried out research across 10 medical centers in the US ( n = 244) and showed that superior outcomes were obtained after treatment with the conventional regimens compared to alternative therapies [ 11 ]. In a multivariate analysis, only loss of ADL was found to be predictive of poorer OS (HR = 2.13).…”
Section: Geriatric Approach To Aggressive Lymphomasmentioning
confidence: 99%
“…The actual incidence of BILI in elderly patients with HL is not known, with variable rates reported due to the use of retrospective study designs and reporting biases [ 11 , 30 , 43 , 51 , 52 ]. Concerning prospective trials, only Evens et al used exact methods for testing pulmonary lung function [ 43 ].…”
Section: Should We Be Afraid Of Bleomycin Use In Elderly Patients Wit...mentioning
confidence: 99%
See 1 more Smart Citation